ABBaH: Activity Breaks for Brain Health. A Protocol for a Randomized Crossover Trial - Heiland, Emerald G.; Ekblom, Örjan; Tarassova, Olga; Fernström, Maria; English, Coralie; Ekblom, Maria M. (Frontiers in Human Neuroscience, 2020)
Introduction: Extended periods of sitting may have detrimental effects on brain health. However, the effects of breaking up prolonged sedentary periods with frequent, short physical activity bouts on mechanisms to improve brain health remain unclear. Therefore, this study aims to investigate the immediate effects of uninterrupted sitting and frequent, short bouts of physical activity on cerebral blood flow and cognitive function in the prefrontal cortex in middle-aged adults. Methods: This is a protocol article to describe a randomized crossover study. We will collect data from 13 healthy adults, aged between 40 and 60 years old, with a body mass index <35 kg/m2. Participants will be required to come into the laboratory on three occasions, sit for 3 h, and perform a different type of break for 3 min every 30 min at each visit in a random order, being either: (1) a social break; (2) brisk walk on a treadmill; or (3) simple resistance activities. Before and after each experimental condition, cerebral blood flow (primary outcome) will be measured using functional near-infrared spectroscopy (fNIRS), with short-separation channels, and working memory (1-, 2-, and 3-back on the computer) will be assessed. The following additional secondary outcomes will be collected: psychological factors (questionnaires); arterial stiffness; salivary cortisol levels; and blood glucose levels. Conclusion: The results from this randomized crossover study will determine the effects of uninterrupted sitting and frequent, short bouts of physical activity on cerebral blood flow and cognitive performance. Publication of this study protocol emphasizes the importance of registration and publication of protocols in the field of sedentary behavior research.